Self-Worth as a Mediator and Moderator Between Teacher-Student Relationships and Student Engagement in Rural Schools - Huang, Jiali; Sang, Guoyuan; Chao, Tzuyang (Frontiers in Psychology, 2022)
This study examined how students’ self-worth mediated and moderated teacher-student relationships and students’ engagement in rural middle schools in China. Eighth grade students (N = 943) completed surveys measuring their perceived relationships with teachers, self-worth, and engagement. Statistical analysis revealed significant correlations (p < .001) among all three variables, with the strongest being between teacher-student relationships and student engagement. Structure equation modeling indicated that self-worth partially mediated the effect of teacher-student relationships on student engagement; however, teacher-student relationship was a stronger predictor. Multi-group analysis identified self-worth as a moderator, whereby students with lower self-worth were more reliant on a positive teacher–student relationships to enhance their engagement with learning. The findings provide important insights for nurturing teacher-student relationships in rural areas.